2001
DOI: 10.1021/om000522n
|View full text |Cite
|
Sign up to set email alerts
|

Pentacoordinate Silyl Cations Stabilized by Coordination with Oxygen Donors: Crystal Structure, Charge Distribution, and Stereodynamics

Abstract: Attempted preparation of neutral hexacoordinate silicon chelates with two OfSi dative bonds (4), in analogy to previously reported bis-NfSi isomers (2), resulted in unexpected formation of pentacoordinate siliconium complexes (5 and 6), characterized by a crystal structure. The barrier for inversion of configuration at silicon was determined by selective inversion recovery NMR measurements: ∆G* ) 20.5 ( 0.2 kcal mol -1 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
17
0
3

Year Published

2002
2002
2008
2008

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 29 publications
3
17
0
3
Order By: Relevance
“…Si-O distance is slightly longer than in the dication dihydrazide complex 17 (1.802 and 1.807 Å), 15 and the amide-side Si-O bond is similar to those reported previously for amide-chelate compounds.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Si-O distance is slightly longer than in the dication dihydrazide complex 17 (1.802 and 1.807 Å), 15 and the amide-side Si-O bond is similar to those reported previously for amide-chelate compounds.…”
supporting
confidence: 88%
“…The volatiles were removed under reduced pressure, and to the remaining crude solid 11b was added 10 mL of hexane and 1.101g (4.66 mmol) 4c. 15 The mixture was kept for 24 h at room temperature, followed by removal of volatiles under reduced pressure (1 mmHg). The remaining oil was treated with 2.…”
Section: Methodsmentioning
confidence: 99%
“…Many have been intramolecularly stabilized by solvation of the cationic center by either unsaturated moieties, [25,26] or by N-, O-, S-, or P-centered Lewis base donors. [8,10,13,14,18,19,21,24] Others have been intermolecularly stabilized through coordination with various solvent molecules. [5-7, 9, 12, 20] Nonetheless, a number of groups have shown that essentially free, uncomplexed silicon, germanium, and tin species can be isolated and structurally characterized.…”
mentioning
confidence: 99%
“…So bindet das nat¸rliche Antibiotikum Vancomycin fest an das C-terminale d-Ala-d-Ala-Fragment in Peptiden, die in Bakterien f¸r die Zellwand-Biosynthese genutzt werden, [1] und zahlreiche Zell-Zell-Erkennungsprozesse beruhen auf der Erkennung der RGD-Sequenz. [3] Mehrere Arbeitsgruppen haben Rezep-tormolek¸le f¸r wichtige Sekund‰rstrukturen geschaffen, die in Peptiden und Proteinen auftreten. [3] Mehrere Arbeitsgruppen haben Rezep-tormolek¸le f¸r wichtige Sekund‰rstrukturen geschaffen, die in Peptiden und Proteinen auftreten.…”
Section: Modulare Bausteine F¸r Die Aminos‰ure-erkennung In Peptidenunclassified
“…Als katalytisch aktive Intermediate sind sie ebenfalls von Bedeutung. [3] Die in der ‹bergangsmetall-Komplexchemie etablierten Dianionen der Verbindungen 1 und 2 vom Typ Sal 2À vierz‰hnige Liganden f¸r die Synthese hochkoordinierter Si-Komplexe wie 4, 5 und 7. Polysilane, die im Skelett hyperkoordinierte Si-Atome enthalten, zeigen zudem einzigartige elektronische und optische Eigenschaften.…”
unclassified